Secondary battery and electronic device
By regulating the surface density of the negative electrode material layer and the content of fluoroethylene carbonate in the electrolyte, a uniform SEI film is formed, which solves the problem of cycle life of lithium-ion batteries under high energy density and low-liquid liquid volume, and reduces gas production in a high-temperature environment and improves circulation performance.
Patent Information
- Application Number
- CN202311279914.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
Under the demand for high energy density, existing lithium-ion batteries are difficult to maintain a long cycle life under the demand for subsistence liquid, and produce more gas in high temperature environments, affecting circulation performance.
By regulating the surface density of the negative electrode material layer and the content of fluoroethylene carbonate in the electrolyte, it is ensured that it is coordinated to control the distribution density of the negative electrode active material and the wetting trend of fluoroethylene carbonate within a certain proportion range, forming a uniform SEI film and reducing electrolyte consumption.
It achieves the high energy density and low liquid retention volume, and the circulation life of the secondary battery is extended, and gas production is reduced in high temperature environments and improved circulation performance.
Smart Images

Figure BDA0004480548600000031 
Figure BDA0004480548600000041 
Figure BDA0004480548600000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a secondary battery and an electronic device. Background Art
[0002] Secondary batteries (such as lithium-ion batteries) are widely used in smart phones, wearable devices, consumer drones, electric vehicles and other fields due to their high energy density, long cycle life and no memory effect. With the widespread application of lithium-ion batteries in the above fields, the market has higher and higher requirements for the energy density and cycle life of lithium-ion batteries.
[0003] With the demand for high energy density, more stringent requirements are placed on the electrolyte retention of lithium-ion batteries. How to ensure that lithium-ion batteries achieve longer cycle life with lower electrolyte retention requirements is one of the main research directions under the current high energy density demand. Summary of the invention
[0004] The purpose of this application is to provide a secondary battery and an electronic device to improve the cycle life of the secondary battery. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a secondary battery, the secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, and the surface density of the single-sided negative electrode material layer is D g / 1540.25 mm 2 , 0.100≤D≤0.180. The electrolyte includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate is A1%, 4.2≤A1≤14.8 based on the mass of the electrolyte. The secondary battery satisfies: 25≤A1 / D≤100. The present application can synergistically control the distribution density of the negative electrode active material, the stacking morphology of the negative electrode active material in the negative electrode sheet and the wetting trend of fluoroethylene carbonate in the negative electrode sheet by regulating the surface density of the single-sided negative electrode material layer and the content of fluoroethylene carbonate within the above range, and making the two satisfy the above-mentioned proportional relationship, so that the negative electrode active materials at different depths from the surface of the negative electrode sheet can have uniform and sufficient contact with fluoroethylene carbonate, so that a uniform and appropriately thick SEI film is formed on the surface of the negative electrode active material, thereby improving the stability of the negative electrode active material during the cycle of the secondary battery, reducing the consumption of the electrolyte during the cycle, and further reducing the liquid retention demand of the secondary battery. The secondary battery in the present application has a high energy density and a low liquid retention volume, and also has a long cycle life.
[0006] In one embodiment of the present application, the electrolyte further comprises ethylene carbonate, propylene carbonate and propyl propionate. Based on the mass of the electrolyte, the sum of the mass percentages of ethylene carbonate and propylene carbonate is S1%, the mass percentage of propyl propionate is S2%, 7≤S1≤12, 30≤S2≤70. By regulating the sum of the mass percentages of ethylene carbonate and propylene carbonate within the scope of the present application, ethylene carbonate and propylene carbonate can be made to uniformly and fully contact the negative electrode active material at different depths from the surface of the negative electrode plate, which is beneficial to the formation of a stable SEI film on the surface of the negative electrode active material, thereby improving the cycle life of the secondary battery; by regulating the mass percentage of propyl propionate within the scope of the present application, the electrolyte has a lower viscosity, which is beneficial to the diffusion of the electrolyte during the cycle, thereby improving the cycle life of the secondary battery.
[0007] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage M1 of ethylene carbonate is 2% to 9.5%, and the mass percentage M2 of propylene carbonate is 2% to 9.5%. By regulating the mass percentage M1 of ethylene carbonate within the scope of the present application, it is beneficial for ethylene carbonate and fluoroethylene carbonate to synergistically act on the surface of the negative electrode active material at different depths from the surface of the negative electrode pole piece to form a high-toughness SEI film rich in organic and inorganic composite components, which is beneficial to suppress the consumption of the electrolyte during the cycle, thereby improving the cycle life of the secondary battery. By regulating the mass percentage M2 of propylene carbonate within the scope of the present application, it is beneficial to fully dissociate the lithium salt in the electrolyte, and to uniformly contact the negative electrode active material and the lithium salt at different depths from the surface of the negative electrode pole piece, further conducting the lithium ion transmission path, and improving the film-forming quality of fluoroethylene carbonate on the surface of the negative electrode active material, thereby improving the cycle life of the secondary battery.
[0008] In one embodiment of the present application, 200≤S2 / D≤650. By adjusting the value of S2 / D within the scope of the present application, it is beneficial to control the viscosity of the electrolyte within a suitable range, further conduct the lithium ion transmission path, and improve the film quality of fluoroethylene carbonate on the surface of the negative electrode active material, thereby improving the cycle life of the secondary battery.
[0009] In one embodiment of the present application, the electrolyte further includes a sulfur-oxygen double bond compound, and the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone, vinyl sulfate, propylene sultone, 3-fluoro-1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 1,2-butane sultone, 1,3-butane sultone, 2,4-butane sultone or 1,3-pentane sultone. Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is S3%, 0.01≤S3≤4.9. Selecting the above-mentioned types of sulfur-oxygen double bond compounds and regulating the mass percentage of the sulfur-oxygen double bond compounds within the scope of the present application is conducive to improving the film quality, thereby improving the cycle life of the secondary battery.
[0010] In one embodiment of the present application, 3≤S3≤4.6. Regulating the mass percentage of the sulfur-oxygen double bond compound within the scope of the present application is beneficial to improving the cycle life of the secondary battery.
[0011] In one embodiment of the present application, the electrolyte further includes nitrile compounds, including at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, heptane dinitrile, octanedinitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, trans-butylenedinitrile, 2-pentene dinitrile, methylglutaronitrile, 4-cyanopeptane dinitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, 1,3,5-pentanetricarbonitrile, 4-(2-cyanoethyl)heptane dinitrile or 1,2,3-tris(2-cyanoethoxy)propane; based on the mass of the electrolyte, the mass percentage of the nitrile compound is S4%, 2.6≤S4≤8.2. Selecting the above-mentioned types of nitrile compounds and regulating the mass percentage of the nitrile compounds within the scope of the present application is conducive to improving the stability of the electrode structure, thereby improving the cycle life of the secondary battery.
[0012] In one embodiment of the present application, the secondary battery satisfies at least one of the following conditions: (1) 4.2≤A1≤8.5; (2) 26.7≤A1 / D≤66.7; (3) 32≤S2≤59. Selecting a secondary battery that satisfies at least one of the above conditions is beneficial to improving the cycle life of the secondary battery.
[0013] In one embodiment of the present application, the secondary battery satisfies at least one of the following conditions: (1) 8.5≤A1≤13.5; (2) 55.6≤A1 / D≤76.9; (3) 238≤S2 / D≤580. Selecting a secondary battery that satisfies at least one of the above conditions is beneficial to improving the cycle life of the secondary battery.
[0014] In one embodiment of the present application, the electrolyte satisfies at least one of the following conditions: (1) the electrolyte includes adiponitrile and ethylene glycol bis(propionitrile) ether; (2) the electrolyte includes ethylene carbonate, propylene carbonate and succinonitrile; (3) the electrolyte includes vinyl sulfate and adiponitrile. (4) the electrolyte includes ethylene carbonate, propylene carbonate and 1,3,6-hexanetrinitrile. Selecting an electrolyte that satisfies at least one of the above conditions is beneficial to improving the cycle life of the secondary battery.
[0015] In one embodiment of the present application, the electrolyte further comprises a compound of formula (I):
[0016]
[0017] Among them, X is selected from CR 6 or N; R 1 , R 2 and R 3 Each is independently selected from a hydrogen atom, a halogen, a C2-C5 carbonyl group, a C1-C5 aldehyde group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, a C2-C5 alkynyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heterocycloalkyl group which is unsubstituted or substituted by Ra, and a C3-C5 N-heteroaryl group. R 4 , R 5 and R 6 Each is independently selected from a hydrogen atom, a C1-C5 alkylthio group, a C2-C5 thioether, a C3-C5 N-heterocycloalkyl group, a C3-C5 N-heteroaryl group, a C1-C5 alkyl group that is unsubstituted or substituted by Ra, a C2-C5 alkenyl group that is unsubstituted or substituted by Ra, and a C2-C5 alkynyl group that is unsubstituted or substituted by Ra; the substituent Ra of each group is independently selected from a halogen, a C1-C5 aldehyde group, a C2-C5 carbonyl group, a C2-C5 ester group, a sulfonic acid group, an amino group, a C2-C5 amide group or a cyano group. Based on the total mass of the electrolyte, the mass percentage of the compound of formula (I) is S5%, 0.01≤S5≤5. Selecting the above-mentioned type of compound of formula (I) and regulating the mass percentage of the compound of formula (I) within the scope of the present application is conducive to the synergistic effect of the compound of formula (I) and fluoroethylene carbonate on the surface of the negative electrode active material to form a stable SEI film with suitable thickness and good ion diffusion performance, reduce the consumption of electrolyte during the cycle process, and thus improve the cycle life of the secondary battery.
[0018] In one embodiment of the present application, the compound of formula (I) is selected from at least one of the following compounds:
[0019]
[0020] The use of the above-mentioned compounds of formula (I) is conducive to forming a stable SEI film with suitable thickness and good ion diffusion performance on the surface of the active material, reducing the consumption of electrolyte during the cycle process, thereby increasing the cycle life of the secondary battery.
[0021] In one embodiment of the present application, the negative electrode material layer includes a negative electrode active material, and the Dv50 of the negative electrode active material is D1 μm, 5≤D1≤25. By regulating the Dv50 of the negative electrode active material within the above range, it is beneficial for the fluoroethylene carbonate to fully contact with the negative electrode material to form a dense SEI film, thereby improving the cycle life of the secondary battery.
[0022] In one embodiment of the present application, the negative electrode material layer includes a negative electrode active material, and the Dv50 of the negative electrode active material is D1 μm, 8≤D1≤15. By adjusting the Dv50 of the negative electrode active material within the above range, it is beneficial to improve the cycle life of the secondary battery.
[0023] In one embodiment of the present application, 0.8≤D×D1≤3.4. By adjusting the value of D×D1 within the above range, the distribution density of the negative electrode active material, the stacking morphology of the negative electrode active material in the negative electrode sheet, and the wetting trend of fluoroethylene carbonate in the negative electrode sheet can be further controlled, thereby taking into account the energy density of the secondary battery while improving the cycle life of the secondary battery.
[0024] In one embodiment of the present application, 1≤D×D1≤3. By adjusting the value of D×D1 within the above range, the energy density of the secondary battery is taken into account while the cycle life of the secondary battery is improved.
[0025] In one embodiment of the present application, the negative electrode material layer includes a negative electrode active material, the number of particles of the negative electrode active material having a sphericity less than or equal to 0.6 and a particle size less than or equal to 10 μm in the negative electrode active material is N1, the total number of particles of the negative electrode active material is N, and N1 / N×100%≤3%. By adjusting the value of N1 / N×100% within the scope of the present application, it is beneficial to control the stacking morphology of the negative electrode active material in the negative electrode sheet, improve the infiltration of the electrolyte, and promote the uniform contact between fluoroethylene carbonate and the negative electrode material particles, thereby improving the cycle life of the secondary battery.
[0026] The second aspect of the present application provides an electronic device, which includes the secondary battery described in any of the above embodiments. The secondary battery of the present application has a long cycle life, so the electronic device of the present application has a long service life.
[0027] Beneficial effects of this application:
[0028] The present application provides a secondary battery and an electronic device. The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector. The surface density of the single-sided negative electrode material layer is D g / 1540.25 mm 2 , 0.100≤D≤0.180; the electrolyte includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate based on the mass of the electrolyte is A1%, 4.2≤A1≤14.8; the secondary battery satisfies: 25≤A1 / D≤100. Fluorinated ethylene carbonate is used as a film-forming additive in the electrolyte to form a protective layer on the surface of the negative electrode active material, improve the stability of the negative electrode solid electrolyte interface (SEI) film, and reduce the side reaction between the electrolyte and the negative electrode active material during the cycle. The present application can coordinately control the distribution density of the negative electrode active material, the stacking morphology of the negative electrode active material in the negative electrode sheet, and the wetting trend of fluoroethylene carbonate in the negative electrode sheet by regulating the surface density of the single-sided negative electrode material layer and the content of fluoroethylene carbonate within the above range and making the two satisfy the above proportional relationship, so that the negative electrode active materials at different depths from the surface of the negative electrode sheet can have uniform and sufficient contact with fluoroethylene carbonate, so that a uniform and appropriately thick SEI film is formed on the surface of the negative electrode active material, thereby improving the stability of the negative electrode active material during the cycle of the secondary battery, reducing the consumption of the electrolyte during the cycle, and further reducing the liquid retention demand of the secondary battery, while improving the room temperature cycle performance of the secondary battery, taking into account the high temperature cycle gas production performance of the secondary battery. The secondary battery in the present application has a high energy density and a low liquid retention volume, and also has a long cycle life.
[0029] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0031] The first aspect of the present application provides a secondary battery, the secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer arranged on at least one surface of the negative electrode current collector, and the surface density of the single-sided negative electrode material layer is D g / 1540.25 mm 2, 0.100≤D≤0.180. For example, the value of D can be 0.100, 0.110, 0.120, 0.130, 0.140, 0.150, 0.160, 0.170, 0.180 or a range consisting of any two of the values therein. The electrolyte includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate (FEC) is A1% based on the mass of the electrolyte, 4.2≤A1≤14.8. In one embodiment of the present application, 4.2≤A1≤8.5; in another embodiment of the present application, 8.5≤A1≤13.5. For example, A1 is 4.2, 4.5, 6, 8, 8.5, 9.5, 10, 12, 13.5, 14, 14.8 or a range consisting of any two of the values therein. The secondary battery satisfies: 25≤A1 / D≤100. In one embodiment of the present application, 26.7≤A1 / D≤66.7; in another embodiment of the present application, 55.6≤A1 / D≤76.9. For example, A1 / D is 25, 26.7, 35, 45, 55, 55.6, 65, 66.7, 75, 76.9, 85, 95, 100, or a range consisting of any two of these values.
[0032] In the prior art, high energy density secondary batteries have a high demand for liquid retention, and it is difficult to achieve a low liquid retention while taking into account its cycle performance. During the normal temperature cycle, as the cycle proceeds, the electrolyte reacts side-effects on the surface of the negative electrode active material and accumulates on the surface of the negative electrode material layer. The lithium ions cannot be normally embedded in the negative electrode material layer, resulting in the occurrence of lithium precipitation, which easily leads to accelerated cycle and even rapid capacity decay of the secondary battery. When the content of the negative electrode active material in the negative electrode material layer is increased, although the energy density of the secondary battery is increased, the internal resistance and polarization of the secondary battery will also increase, the side reactions on the surface of the negative electrode material layer will intensify, and the electrolyte consumption will increase while the cycle performance will be further reduced. Fluorinated ethylene carbonate is used as a film-forming additive in the electrolyte to form a protective layer on the surface of the negative electrode active material, improve the stability of the negative electrode solid electrolyte interface (SEI) film, and reduce the side reactions between the electrolyte and the negative electrode active material during the cycle. When the content of fluoroethylene carbonate is too high, the secondary battery produces more gas in a high temperature (≥45°C) environment, which reduces the high temperature intermittent cycle gas production performance of the secondary battery. The present application controls the weight of the negative electrode material layer and the content of fluoroethylene carbonate within the scope of the present application, and makes the two satisfy the above-mentioned proportional relationship, so as to coordinately control the distribution density of the negative electrode active material, the stacking form of the negative electrode active material in the negative electrode sheet and the wetting trend of fluoroethylene carbonate in the negative electrode sheet, so that the negative electrode active materials at different depths from the surface of the negative electrode sheet can have uniform and sufficient contact with fluoroethylene carbonate, so that a uniform and appropriately thick SEI film is formed on the surface of the negative electrode active material, while improving the room temperature cycle performance of the secondary battery, taking into account the high temperature intermittent cycle gas production performance of the secondary battery. The secondary battery in the present application has a long cycle life while having high energy density and low liquid retention. Among them, the surface density D of the single-sided negative electrode material layer in the present application can be regulated by means known to those skilled in the art. For example, when the negative electrode slurry is coated on the surface of the negative electrode current collector, on the basis of a certain solid content of the negative electrode slurry, the coating amount of the negative electrode slurry is increased to increase D. The present application is not particularly limited, as long as the purpose of the present application can be achieved.
[0033] In one embodiment of the present application, the electrolyte further comprises ethylene carbonate (EC), propylene carbonate (PC), and propyl propionate (PP). Based on the mass of the electrolyte, the sum of the mass percentages of ethylene carbonate and propylene carbonate is S1%, the mass percentage of propyl propionate is S2%, 7≤S1≤12, 30≤S2≤70. Preferably, 32≤S2≤59. For example, S1 is 7, 8, 9, 10, 11, 12, or a range consisting of any two of the values, and S2 is 30, 39, 40, 50, 59, 60, 70, or a range consisting of any two of the values. By regulating the sum of the mass percentages of ethylene carbonate and propylene carbonate within the scope of the present application, the electrolyte has a good ability to dissociate lithium salts and is conducive to forming a stable SEI film on the surface of the negative electrode, thereby improving the cycle life of the secondary battery; by regulating the mass percentage of propyl propionate within the scope of the present application, the electrolyte has a lower viscosity, which is conducive to the diffusion of the electrolyte during the cycle, thereby improving the cycle life of the secondary battery.
[0034] In one embodiment of the present application, based on the mass of the electrolyte, the mass percentage content M1 of ethylene carbonate is 2% to 9.5%, and the mass percentage content M2 of propylene carbonate is 2% to 9.5%. For example, the mass percentage content M1 of ethylene carbonate is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or a range consisting of any two of the values, and the mass percentage content M2 of propylene carbonate is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or a range consisting of any two of the values. By regulating the mass percentage content M1 of ethylene carbonate within the scope of the present application, it is beneficial for ethylene carbonate and fluoroethylene carbonate to synergistically act on the surface of the negative electrode active material at different depths from the surface of the negative electrode plate, forming a high-toughness SEI film rich in organic and inorganic composite components, which is beneficial to suppress the consumption of electrolyte during the cycle, thereby improving the cycle life of the secondary battery. By regulating the mass percentage content M2 of propylene carbonate within the scope of the present application, it is beneficial to the full dissociation of lithium salt in the electrolyte, and to the uniform contact between the negative electrode active material and the lithium salt at different depths from the surface of the negative electrode plate, further opening the lithium ion transmission path, and improving the film formation quality of fluoroethylene carbonate on the surface of the negative electrode material, thereby improving the room temperature cycle performance of the secondary battery while taking into account the high temperature intermittent cycle gas production performance of the secondary battery.
[0035] In one embodiment of the present application, 15≤A1+S1≤25. For example, A1+S1 is 15, 17, 19, 21, 23, 25 or a range consisting of any two of these values. By regulating the value of A1+S1 within the scope of the present application, it is beneficial for ethylene carbonate and fluoroethylene carbonate to work synergistically, and a stable SEI film with an organic and inorganic composite and a suitable proportion is formed on the surface of the negative electrode. The electrolyte has a good ability to dissociate lithium salts, which reduces the consumption of electrolyte during the cycle, thereby improving the cycle life of the secondary battery.
[0036] In one embodiment of the present application, 200≤S2 / D≤650. Preferably, 238≤S2 / D≤580. For example, S2 / D is 200, 238, 250, 300, 350, 400, 450, 500, 550, 580, 600, 650 or a range consisting of any two of these values. By regulating the value of S2 / D within the scope of the present application, it is beneficial to control the viscosity of the electrolyte within a suitable range, further conduct the lithium ion transmission path, and improve the film quality of fluoroethylene carbonate on the surface of the negative electrode active material, thereby improving the cycle life of the secondary battery.
[0037] In one embodiment of the present application, the electrolyte further includes a sulfur-oxygen double bond compound, and the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone, vinyl sulfate, propene sultone, 3-fluoro-1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 1,2-butane sultone, 1,3-butane sultone, 2,4-butane sultone or 1,3-pentane sultone. Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is S3%, 0.01≤S3≤4.9. Preferably, 3≤S3≤4.6. For example, S3 is 0.01, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.6, 4.9 or a range consisting of any two of the values. Selecting the above-mentioned types of sulfur-oxygen double bond compounds and regulating the mass percentage of the sulfur-oxygen double bond compounds within the scope of the present application is beneficial to improving the film-forming quality, thereby increasing the cycle life of the secondary battery.
[0038] In one embodiment of the present application, the electrolyte further includes nitrile compounds, and the nitrile compounds include at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, heptane dinitrile, suberonitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, trans-butylenedinitrile, 2-pentene dinitrile, methylglutaronitrile, 4-cyanoheptane dinitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, 1,3,5-pentanetricarbonitrile, 4-(2-cyanoethyl) heptane dinitrile or 1,2,3-tris(2-cyanoethoxy)propane; based on the mass of the electrolyte, the mass percentage of the nitrile compound is S4%, 2.6≤S4≤8.2. For example, S4 is 2.6, 3, 4, 5, 6, 7, 8, 8.2 or a range consisting of any two of the values. Selecting the above-mentioned types of nitrile compounds and regulating the mass percentage of the nitrile compounds within the scope of the present application is beneficial to improving the stability of the electrode structure, thereby increasing the cycle life of the secondary battery.
[0039] In one embodiment of the present application, the electrolyte further comprises a compound of formula (I):
[0040]
[0041] Among them, X is selected from CR 6 or N; R 1 , R 2 and R 3 Each is independently selected from a hydrogen atom, a halogen, a C2-C5 carbonyl group, a C1-C5 aldehyde group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, a C2-C5 alkynyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heterocycloalkyl group which is unsubstituted or substituted by Ra, and a C3-C5 N-heteroaryl group. R 4 , R 5 and R 6 Each is independently selected from a hydrogen atom, a C1-C5 alkylthio group, a C2-C5 thioether, a C3-C5 N-heterocycloalkyl group, a C3-C5 N-heteroaryl group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, and a C2-C5 alkynyl group which is unsubstituted or substituted by Ra; wherein the C1-C5 alkylthio group is also RS-, and R is a C1-C5 alkyl group.
[0042] The substituent Ra of each group is independently selected from halogen, C1-C5 aldehyde group, C2-C5 carbonyl group, C2-C5 ester group, sulfonic acid group, amino group, C2-C5 amide group or cyano group. Based on the total mass of the electrolyte, the mass percentage of the compound of formula (I) is S5%, 0.01≤S5≤5. For example, S5 is 0.01, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or a range consisting of any two of the values. Selecting the above-mentioned types of compounds of formula (I) and regulating the mass percentage of the compounds of formula (I) within the scope of this application is conducive to the synergistic effect of the compounds of formula (I) and fluoroethylene carbonate on the surface of the negative electrode active material to form a stable SEI film with suitable thickness and good ion diffusion performance, reducing the consumption of electrolyte during the cycle, thereby improving the cycle life of the secondary battery.
[0043] In one embodiment of the present application, R 1 , R 2 and R 3 R is independently selected from hydrogen, -F, -Cl, -Br, -I, formaldehyde, acetaldehyde, ethylcarbonyl, propylcarbonyl, methyl, ethyl, propyl, butyl, vinyl, propenyl, butenyl, ethynyl, propynyl, butynyl, pyrrolyl or pyridyl; 4 , R 5 and R 6 Each is independently selected from a hydrogen atom, a methylthio group, a dimethyl sulfide group, a methyl group, an ethyl group, a propyl group, a butyl group, a vinyl group, a propenyl group, a butenyl group, an ethynyl group, a propynyl group, a butynyl group, a pyrrolyl group or a pyridyl group. The electrolyte comprising the compound of formula (I) having a group within the above range is applied to a secondary battery, which is beneficial for the compound of formula (I) to synergistically act with fluoroethylene carbonate on the surface of the negative electrode active material, thereby improving the film quality, reducing the consumption of the electrolyte during the cycle, and thus increasing the cycle life of the secondary battery.
[0044] In one embodiment of the present application, the compound of formula (I) is selected from at least one of the following compounds:
[0045]
[0046] The use of the above-mentioned compounds of formula (I) is conducive to forming a stable SEI film with suitable thickness and good ion diffusion performance on the surface of the active material, reducing the consumption of electrolyte during the cycle process, thereby increasing the cycle life of the secondary battery.
[0047] In one embodiment of the present application, the negative electrode material layer includes a negative electrode active material, and the Dv50 of the negative electrode active material is D1μm, 5≤D1≤25. Preferably, 8≤D1≤15. For example, D1 is 5, 8, 12, 15, 19, 20, 25 or a range consisting of any two of these values. By regulating the Dv50 of the negative electrode active material within the above range, it is beneficial for fluoroethylene carbonate to fully contact with the negative electrode active material to form a dense SEI film, thereby improving the cycle life of the secondary battery. Among them, the Dv50 of the negative electrode active material in the present application can be regulated by means known to those skilled in the art, for example, the negative electrode active material is crushed, graded and shaped, and the present application is not particularly limited, as long as the purpose of the present application can be achieved.
[0048] In one embodiment of the present application, 0.8≤D×D1≤3.4. Preferably, 1≤D×D1≤3. D×D1 is 0.8, 1.0, 1.2, 1.5, 2.0, 2.5, 3.0, 3.2, 3.4 or a range consisting of any two of these values. By regulating the value of D×D1 within the above range, the distribution density of the negative electrode active material, the stacking morphology of the negative electrode active material in the negative electrode sheet and the wetting trend of fluoroethylene carbonate in the negative electrode sheet can be further controlled, thereby improving the cycle life of the secondary battery while taking into account the energy density of the secondary battery.
[0049] In one embodiment of the present application, the negative electrode material layer includes a negative electrode active material, the number of particles of the negative electrode active material having a sphericity less than or equal to 0.6 and a particle size less than or equal to 10 μm in the negative electrode active material is N1, the total number of particles of the negative electrode active material is N, and N1 / N×100%≤3%. For example, N1 / N×100% is 1%, 1.2%, 1.5%, 2%, 2.3%, 2.5%, 2.7%, 3% or a range consisting of any two of the values. By regulating the value of N1 / N×100% within the scope of the present application, by regulating the value of N1 / N×100% within the scope of the present application, it is beneficial to control the stacking morphology of the negative electrode active material in the negative electrode sheet, improve the infiltration of the electrolyte, and promote the uniform contact between fluoroethylene carbonate and the negative electrode material particles, thereby improving the cycle life of the secondary battery. Among them, the particle sphericity of the negative electrode active material in the present application can be regulated by means known to those skilled in the art, for example, the negative electrode active material is crushed and graded, and the present application is not particularly limited, as long as the purpose of the present application can be achieved. In one embodiment of the present application, the electrolyte also includes a lithium salt compound, and the lithium salt compound includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium trifluoromethanesulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium bis oxalate borate or lithium difluoro oxalate borate. Based on the mass of the electrolyte, the mass percentage content S6 of the lithium salt compound is 10% to 20%. For example, the mass percentage content S6 of the lithium salt compound is 10%, 12%, 14%, 16%, 18%, 20% or a range consisting of any two of the values. Selecting the above-mentioned types of lithium salt compounds and regulating the mass percentage content of the lithium salt compounds within the scope of the present application is conducive to providing conductive ions while forming a stable SEI film on the surface of the negative electrode sheet, thereby improving the cycle life of the secondary battery.
[0050] In one embodiment of the present application, the electrolyte includes adiponitrile and ethylene glycol bis(propionitrile) ether; in another embodiment of the present application, the electrolyte includes ethylene carbonate, propylene carbonate and succinonitrile; in yet another embodiment of the present application, the electrolyte includes vinyl sulfate and adiponitrile. In yet another embodiment of the present application, the electrolyte includes ethylene carbonate, propylene carbonate and 1,3,6-hexanetrinitrile. The selection of the electrolyte that meets the above conditions is conducive to improving the cycle life of the secondary battery. In one embodiment of the present application, the electrolyte in the present application also includes a non-aqueous solvent. The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of a carbonate compound, an ether compound or other organic solvents. The carbonate compound may include but is not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate. The ether compound may include, but is not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. Other organic solvents may include, but are not limited to, at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the mass percentage content S7 of the non-aqueous solvent, as long as the purpose of the present application can be achieved. Exemplarily, based on the mass of the electrolyte, the mass percentage content of the non-aqueous solvent S7 is 0% to 85.8%. For example, the mass percentage content S7 of the non-aqueous solvent is 0%, 10%, 20%, 30%, 40%, 44%, 45%, 48%, 49%, 50%, 60%, 65%, 70%, 80%, 85% or a range consisting of any two of these values.
[0051] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, a lithium salt compound and a non-aqueous solvent, the mass percentage of fluoroethylene carbonate and the lithium salt compound is as described above, and the mass percentage of the non-aqueous solvent S7 is 65.2% to 85.8%. The secondary battery including the above electrolyte has a longer cycle life. In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, a lithium salt compound and a non-aqueous solvent, the mass percentage of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate and the lithium salt compound is as described above, and the mass percentage of the non-aqueous solvent S7 is 0% to 48.8%. The secondary battery including the above electrolyte has a longer cycle life.
[0052] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, sulfur-oxygen double bond compound, lithium salt compound and non-aqueous solvent, the mass percentage of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, sulfur-oxygen double bond compound and lithium salt compound is as described above, and the mass percentage of non-aqueous solvent S7 is 0% to 48.79%. The secondary battery including the above electrolyte has a long cycle life.
[0053] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, sulfur-oxygen double bond compounds, nitrile compounds, lithium salt compounds and non-aqueous solvents, and the mass percentages of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, sulfur-oxygen double bond compounds and nitrile compounds are as described above, and the mass percentage S7 of the non-aqueous solvent is 0% to 46.39%. The secondary battery including the above electrolyte has a long cycle life.
[0054] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, sulfur oxygen double bond compound, nitrile compound, compound of formula (I), lithium salt compound and non-aqueous solvent, and the mass percentage of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, sulfur oxygen double bond compound, nitrile compound, compound of formula (I) and lithium salt compound is as described above, and the mass percentage of non-aqueous solvent S7 is 0% to 46.38%. The secondary battery including the above electrolyte has a long cycle life.
[0055] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, a sulfur-oxygen double bond compound, a lithium salt compound and a non-aqueous solvent, the mass percentage of fluoroethylene carbonate, the sulfur-oxygen double bond compound and the lithium salt compound is as described above, and the mass percentage S7 of the non-aqueous solvent is 60.3% to 85.79%. The secondary battery including the above electrolyte has a long cycle life.
[0056] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, nitrile compounds, lithium salt compounds and non-aqueous solvents, the mass percentages of fluoroethylene carbonate, nitrile compounds and lithium salt compounds are as described above, and the mass percentage S7 of the non-aqueous solvent is 57.2% to 83.4%. The secondary battery including the above electrolyte has a long cycle life.
[0057] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, a compound of formula (I), a lithium salt compound and a non-aqueous solvent, wherein the mass percentage of fluoroethylene carbonate, the compound of formula (I) and the lithium salt compound is as described above, and the mass percentage of the non-aqueous solvent S7 is 60.2% to 85.79%. The secondary battery including the above electrolyte has a long cycle life.
[0058] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, nitrile compounds, lithium salt compounds and non-aqueous solvents, and the mass percentages of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, nitrile compounds and lithium salt compounds are as described above, and the mass percentage S7 of the non-aqueous solvent is 0% to 46.4%. The secondary battery including the above electrolyte has a long cycle life.
[0059] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, a compound of formula (I), a lithium salt compound and a non-aqueous solvent, and the mass percentage of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, propyl propionate, a compound of formula (I) and a lithium salt compound is as described above, and the mass percentage of the non-aqueous solvent S7 is 0% to 48.79%. The secondary battery including the above electrolyte has a long cycle life. The secondary battery including the above electrolyte has a long cycle life.
[0060] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, sulfur-oxygen double bond compound, nitrile compound, lithium salt compound and non-aqueous solvent, the mass percentage of fluoroethylene carbonate, sulfur-oxygen double bond compound, nitrile compound and lithium salt compound is as described above, and the mass percentage of non-aqueous solvent S7 is 52.3% to 83.39%. The secondary battery including the above electrolyte has a long cycle life.
[0061] In one embodiment of the present application, the electrolyte may include fluoroethylene carbonate, a sulfur-oxygen double bond compound, a compound of formula (I), a lithium salt compound, and a non-aqueous solvent, wherein the mass percentages of fluoroethylene carbonate, the sulfur-oxygen double bond compound, the compound of formula (I), and the lithium salt compound are as described above, and the mass percentage S7 of the non-aqueous solvent is 55.3% to 85.78%. The secondary battery including the above electrolyte has a long cycle life.
[0062] In an embodiment of the present application, the electrolyte may include fluoroethylene carbonate, a nitrile compound, a compound of formula (I), a lithium salt compound, and a non-aqueous solvent. The mass percentage contents of fluoroethylene carbonate, the nitrile compound, the compound of formula (I), and the lithium salt compound are as described above, and the mass percentage content S7 of the non-aqueous solvent is 52.2% to 83.39%. The secondary battery including the above electrolyte has a long cycle life.
[0063] In an embodiment of the present application, the electrolyte may include fluoroethylene carbonate, a thiocarbonyl double bond compound, a nitrile compound, a compound of formula (I), a lithium salt compound, and a non-aqueous solvent. The mass percentage contents of fluoroethylene carbonate, the thiocarbonyl double bond compound, the nitrile compound, the compound of formula (I), and the lithium salt compound are as described above, and the mass percentage content S7 of the non-aqueous solvent is 47.3% to 83.38%. The secondary battery including the above electrolyte has a long cycle life.
[0064] In the present application, the "negative electrode material layer disposed on at least one surface of the negative electrode current collector" means that the negative electrode material layer may be disposed on one surface of the negative electrode current collector along its own thickness direction, or may be disposed on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here may be the entire area of the surface of the negative electrode current collector, or may be a partial area of the surface of the negative electrode current collector. There is no particular limitation in the present application as long as the object of the present application can be achieved. There is no particular limitation on the negative electrode current collector in the present application as long as the object of the present application can be achieved. For example, the negative electrode current collector may include a copper foil, a copper alloy foil, a nickel foil, a stainless steel foil, a titanium foil, a nickel foam, a copper foam, or a composite current collector (such as a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.). There is no particular limitation on the type of the negative electrode active material in the present application as long as the object of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, a silicon-carbon composite, SiO x (0 < x < 2), a Li-Sn alloy, a Li-Sn-O alloy, Sn, SnO, SnO 2 、spinel-structured lithium titanate Li 4 Ti 5 O 12, Li-Al alloy or metallic lithium. In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 20μm, and the thickness of the negative electrode material layer is 30μm to 130μm. Optionally, the negative electrode material layer may also include a conductive agent and a negative electrode binder. The present application does not particularly limit the type of conductive agent in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials or conductive polymers. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application does not particularly limit the type of negative electrode binder in the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinyl pyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The present application does not particularly limit the mass ratio of the negative electrode active material, the conductive agent and the negative electrode binder in the negative electrode material layer, as long as the purpose of the present application can be achieved.
[0065] The present application has no special restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet includes a positive current collector and a positive electrode material layer arranged on at least one surface of the positive current collector. The above-mentioned "positive electrode material layer arranged on at least one surface of the positive current collector" means that the positive electrode material layer can be arranged on one surface of the positive current collector along its own thickness direction, or it can be arranged on two surfaces of the positive current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive current collector, or it can be a partial area of the surface of the positive current collector. The present application has no special restrictions, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the positive current collector, as long as the purpose of the present application can be achieved. For example, the positive current collector may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The positive electrode material layer of the present application includes a positive electrode active material, and the present application has no special restrictions on the type of positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO 2 ), lithium manganate, lithium manganese iron phosphate or lithium titanate, etc. In the present application, the positive electrode active material may also contain non-metallic elements, for example, the non-metallic elements include at least one of fluorine, phosphorus, boron, chlorine, silicon or sulfur. In the present application, there is no particular restriction on the thickness of the positive current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is 5μm to 20μm, preferably 6μm to 18μm. The thickness of the single-sided positive electrode material layer is 30μm to 120μm. In the present application, the positive electrode material layer may also include a conductive agent and a positive electrode binder. The present application does not particularly limit the type of conductive agent in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may be the same as the type of conductive agent in the above-mentioned negative electrode material layer. The present application does not particularly limit the type of positive electrode binder in the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may be the same as the type of positive electrode binder in the above-mentioned positive electrode material layer. The present application has no particular restriction on the mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can select the ratio according to actual needs as long as the purpose of the present application can be achieved.
[0066] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or at least one of aramid. The type of diaphragm may include at least one of woven membranes, non-woven membranes, microporous membranes, composite membranes, rolled membranes or spun membranes. The diaphragm of the present application may have a porous structure, and the present application has no particular restrictions on the size of the pore size of the porous structure of the diaphragm, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01μm to 1μm. The present application has no particular restrictions on the thickness of the diaphragm, as long as the purpose of the present application can be achieved. For example, the thickness of the diaphragm can be 4μm to 500μm.
[0067] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0068] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. For example, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a sodium ion secondary battery (sodium ion battery), a lithium polymer secondary battery, and a lithium ion polymer secondary battery.
[0069] The present application does not particularly limit the preparation method of the secondary battery, and the preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the secondary battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery.
[0070] The second aspect of the present application provides an electronic device, which includes the secondary battery described in any of the above embodiments. The secondary battery of the present application has a long cycle life, so the electronic device of the present application has a long service life.
[0071] The electronic device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor.
[0072] Example
[0073] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods.
[0074] Test methods and equipment:
[0075] Negative electrode active material Dv50 test:
[0076] The negative electrode material layer was scraped off from the negative electrode current collector in each embodiment or comparative example, and the scraped negative electrode material layer was heat treated at 400° C. for 4 hours in a tube furnace under argon protection to obtain a powder. 0.02 g of the obtained powder was placed in a 50 mL clean beaker, 20 mL of deionized water was added, and 0.2 mL of a surfactant sodium dodecyl sulfate was added dropwise to completely disperse the powder in the deionized water, and ultrasonicated in a 120 W ultrasonic cleaning machine for 5 minutes, and the particle size distribution was tested using a MasterSizer 2000, and the diameter corresponding to the cumulative volume fraction of the particles in the volume reference distribution reached 50% was obtained by testing with a laser scattering particle size analyzer.
[0077] Negative electrode active material sphericity test:
[0078] Use an electron scanning microscope to magnify the number of negative electrode active material particles observed to be n (n≥100), randomly select 100 from the n negative electrode active material particles, use a particle imaging workstation to measure the above 100 negative electrode active material particles respectively, and measure the minimum diameter r and maximum diameter R of the negative electrode active material particles. The sphericity calculation formula is: e=r / R, and the particle size of the negative electrode active material=(r+R) / 2.
[0079] The number of negative electrode active material particles having a sphericity of less than or equal to 0.6 and an average diameter of less than or equal to 10 μm is N1, the total number of negative electrode active material particles is N, and the value of N1 / N in each embodiment or comparative example is calculated.
[0080] Normal temperature cycle performance test:
[0081] At 25°C, charge the lithium-ion battery to 4.25V at 1.2C constant current, charge at 4.25V constant voltage to 0.7C, then charge at 0.7C constant current to 4.5V, charge at 4.5V constant voltage to 0.05C, let stand for 5 minutes, and then discharge at 0.5C constant current to 3.0V. This is the first cycle, and the discharge capacity is recorded. Perform multiple cycles according to the above cycle process, and measure the discharge capacity of the lithium-ion battery after each cycle. With the capacity of the first discharge as 100%, repeat the charge and discharge cycle until the discharge capacity retention rate decays to 80% of the first discharge capacity, stop the test, and record the number of cycles as an indicator for evaluating the capacity retention rate of the lithium-ion battery at room temperature.
[0082] Capacity retention rate = (discharge capacity after each cycle / discharge capacity at the first cycle) × 100%.
[0083] High temperature intermittent cycle (ITC) gas production test:
[0084] At 45°C, charge the lithium-ion battery to 4.5V at a constant current of 0.5C, charge at a constant voltage of 4.5V to a current of 0.05C, and use a micrometer to test the thickness of the battery cell, which is the initial thickness; after standing at 45°C for 19.5h, discharge at a constant current of 0.5C to 3.0V. Perform multiple cycles according to the above cycle process, and measure the thickness of the lithium-ion battery after each constant voltage charging. Calculate the thickness expansion rate according to the following formula. When the thickness expansion rate reaches 10%, stop the test and record the number of cycles, which is the number of high-temperature intermittent cycles, as an indicator for evaluating the gas production of lithium-ion batteries during high-temperature intermittent cycles.
[0085] Thickness expansion rate = (thickness after each cycle of constant voltage charging - initial thickness) / initial thickness × 100%.
[0086] The greater the number of high-temperature intermittent cycles, the better the high-temperature intermittent cycle gas production performance of the lithium-ion battery, and the less gas production of the lithium-ion battery; when the smaller the number of high-temperature intermittent cycles, the worse the high-temperature intermittent cycle gas production performance of the lithium-ion battery, and the greater the gas production of the lithium-ion battery.
[0087] Example 1-1
[0088] <Preparation of Electrolyte>
[0089] In an argon atmosphere glove box with a water content of less than 10 ppm, fluoroethylene carbonate (FEC) and a non-aqueous solvent diethyl carbonate (DEC) were mixed to obtain a base solvent, and then a lithium salt compound LiPF was added to the base solvent. 6 , and stir evenly to obtain an electrolyte. Among them, based on the mass of the electrolyte, LiPF6 The mass percentage of FEC is 12%, and the mass percentage of FEC is A 1 is 10%.
[0090] <Preparation of negative electrode sheet>
[0091] The negative electrode active material graphite, the negative electrode binder styrene-butadiene rubber, and the negative electrode thickener sodium carboxymethyl cellulose are mixed in a mass ratio of 95:2:3, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 75wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 5μm, and dried at 85°C for 4 hours to obtain a negative electrode sheet with a single-sided negative electrode material layer coated with a width of 76.6mm. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer coated. Then, after drying under vacuum conditions at 85°C for 4 hours, a negative electrode sheet with a specification of 76.6mm×875mm is obtained by cold pressing, cutting, and slitting. Among them, the surface density D of the single-sided negative electrode material layer is 0.150g / 1540.25mm 2 The negative electrode active material is ground, classified and shaped to obtain a negative electrode active material with a Dv50, ie, D1, of 15 μm.
[0092] <Preparation of positive electrode sheet>
[0093] The positive electrode active material LiCoO 2 , conductive carbon black, and positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 70wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried at 85°C for 4 hours to obtain a positive electrode sheet with a single-sided positive electrode material layer coated with a coating thickness of 110μm and a width of 74mm. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet with a double-sided positive electrode material layer coated. Then, after drying under vacuum conditions at 85°C for 4 hours, a positive electrode sheet with a specification of 74mm×867mm is obtained by cold pressing, cutting, and slitting.
[0094] <Preparation of Separator>
[0095] PVDF and alumina ceramics were mixed in a mass ratio of 1:2, NMP was added as a solvent, and a ceramic layer slurry with a solid content of 12wt% was prepared. The slurry was evenly coated on one surface of a polyethylene substrate with a thickness of 5μm. After drying, a diaphragm with a single-sided alumina ceramic layer with a thickness of 2μm was obtained. PVDF was added to the NMP solvent and stirred evenly to prepare a PVDF slurry with a solid content of 25wt%, and then 0.15mg / cm 2 The PVDF was dried at 85℃ for 4h, and then 0.15mg / cm 2 The PVDF was dried at 85°C for 4 h to obtain a membrane.
[0096] <Preparation of lithium-ion batteries>
[0097] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, so that the side of the separator coated with alumina ceramic layer and PVDF faces the positive electrode sheet, and the side coated with only PVDF faces the negative electrode sheet, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and then wound to obtain an electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, placed in a vacuum oven at 85°C for 12 hours to remove moisture, and the above-prepared electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0098] Example 1-2 to Example 1-10
[0099] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. Among them, when the mass percentage content A1 of fluoroethylene carbonate changes, the mass percentage content of the non-aqueous solvent changes accordingly, and the mass percentage content of the lithium salt compound remains unchanged. When D changes, the coating amount of the negative electrode slurry is adjusted so that the surface density D of the single-sided negative electrode material layer is as shown in Table 1.
[0100] Example 2-1 to Example 2-14
[0101] Examples 2-1 to 2-13 are the same as Example 1-1 except that ethylene carbonate, propylene carbonate and propyl propionate are added in <Preparation of electrolyte> and relevant preparation parameters are adjusted according to Table 2. Example 2-14 is the same as Example 1-7 except that ethylene carbonate, propylene carbonate and propyl propionate are added in <Preparation of electrolyte> and relevant preparation parameters are adjusted according to Table 2. Among them, when at least one of the mass percentage content M1 of ethylene carbonate, the mass percentage content M2 of propylene carbonate, the sum of the mass percentage content S1 of ethylene carbonate and propylene carbonate, or the mass percentage content S2 of propyl propionate changes, the mass percentage content of the non-aqueous solvent changes accordingly, and the mass percentage content of the lithium salt compound remains unchanged.
[0102] Example 3-1 to Example 3-19
[0103] The same as Example 1-1 except that one of the sulfur-oxygen double bond compound, the nitrile compound or the compound of formula (I) is added in <Preparation of the electrolyte> and the relevant preparation parameters are adjusted according to Table 3. Among them, when the mass percentage content S3 of the sulfur-oxygen double bond compound, the mass percentage content S4 of the nitrile compound or the mass percentage content S5 of the compound of formula (I) changes, the mass percentage content of the non-aqueous solvent changes accordingly, and the mass percentage content of the lithium salt compound remains unchanged.
[0104] Example 4-1 to Example 4-10
[0105] Except for adding at least two of ethylene carbonate, propylene carbonate and propyl propionate, sulfur-oxygen double bond compound, nitrile compound or compound of formula (I) in <Preparation of electrolyte>, and adjusting relevant preparation parameters according to Table 4, the rest is the same as Example 1-1. Among them, when at least one of the mass percentage content M1 of ethylene carbonate, the mass percentage content M2 of propylene carbonate, the sum of the mass percentage content S1 of ethylene carbonate and propylene carbonate, the mass percentage content S2 of propyl propionate, the mass percentage content S3 of sulfur-oxygen double bond compound, the mass percentage content S4 of nitrile compound or the mass percentage content S5 of compound of formula (I) changes, the mass percentage content of non-aqueous solvent changes accordingly, and the mass percentage content of lithium salt compound remains unchanged.
[0106] Example 5-1 to Example 5-10
[0107] Except for adjusting the relevant preparation parameters according to Table 5, the rest is the same as Example 1-1. Among them, when D1 and N1 change, the time of crushing and shaping is adjusted so that the values of D1 and N1 are as shown in Table 5.
[0108] Comparative Examples 1 to 5
[0109] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. When the mass percentage A1 of fluoroethylene carbonate changes, the mass percentage of the non-aqueous solvent changes accordingly, and the mass percentage of the lithium salt compound remains unchanged.
[0110] Comparative Example 6
[0111] Except that the electrolyte was prepared using the following <Preparation of electrolyte> steps, the rest was the same as Example 1-1.
[0112] <Preparation of Electrolyte>
[0113] In an argon atmosphere glove box with a water content of less than 10 ppm, ethylene carbonate, propylene carbonate and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1 to obtain a base solvent, and then lithium salt LiPF was added to the base solvent. 6 , and stir evenly to obtain an electrolyte. Among them, based on the mass of the electrolyte, LiPF 6 The mass percentage of tantalum is 12%, the mass percentage of ethylene carbonate is 5%, and the mass percentage of diethyl carbonate is 78%.
[0114] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 5.
[0115] Table 1
[0116]
[0117]
[0118] Note: “ / ” in Table 1 means there is no corresponding parameter or substance.
[0119] From Examples 1-1 to 1-10 and Comparative Examples 1 to 6, it can be seen that the present application regulates the surface density of the single-sided negative electrode material layer and the content of fluoroethylene carbonate within the scope of the present application, and makes the two satisfy the proportional relationship of the present application, and the lithium-ion battery has more high-temperature intermittent cycles and more normal temperature cycles, thereby indicating that the lithium-ion battery has better cycle performance. The content of fluoroethylene carbonate in Comparative Examples 1 to 2 is not within the scope of the present application, the surface density of the single-sided negative electrode material layer in Comparative Examples 3 to 4 is not within the scope of the present application, the ratio of the content of fluoroethylene carbonate to the surface density of the single-sided negative electrode material layer in Comparative Example 5 is not within the scope of the present application, and the electrolyte in Comparative Example 6 does not include fluoroethylene carbonate. Compared with Examples 1-1 to 1-10, the lithium-ion battery in the embodiment of the present application has more high-temperature intermittent cycles and more normal temperature cycles, thereby indicating that the lithium-ion battery has better cycle performance.
[0120] Table 2
[0121]
[0122] Note: “ / ” in Table 2 means there is no corresponding parameter or substance.
[0123] Table 3
[0124]
[0125]
[0126] Note: " / " in Table 3 indicates that there is no corresponding parameter or substance. In Examples 3-8, the nitrile compound is adiponitrile + ethylene glycol bis(propionitrile) ether, which means that the nitrile compound is adiponitrile and ethylene glycol bis(propionitrile) ether; S4 is 2+3, which means that based on the mass of the electrolyte, the mass percentage of adiponitrile is 2%, the mass percentage of ethylene glycol bis(propionitrile) ether is 3%, and the mass percentage of the nitrile compound is 5%. The same applies to other examples.
[0127] Table 4
[0128]
[0129]
[0130] Note: “ / ” in Table 4 means there is no corresponding parameter or substance.
[0131] The mass percentage of ethylene carbonate, propylene carbonate and propyl propionate usually affects the cycle performance of lithium-ion batteries. It can be seen from Examples 1-1, 2-1 to 2-14 that when the mass percentage of ethylene carbonate, propylene carbonate and propyl propionate is within the scope of this application, the number of high-temperature intermittent cycles of the lithium-ion battery is slightly reduced compared with Example 1-1, and the number of normal-temperature cycles is significantly increased, indicating that regulating the mass percentage of ethylene carbonate, propylene carbonate and propyl propionate within the scope of this application is conducive to improving the normal-temperature cycle performance of the lithium-ion battery while taking into account the high-temperature intermittent cycle gas production performance of the secondary battery, indicating that the lithium-ion battery has good cycle performance.
[0132] The type and mass percentage of the sulfur-oxygen double bond compound usually affect the cycle performance of the lithium-ion battery. It can be seen from Examples 1-1 and 3-1 to 3-5 that when the type and mass percentage of the sulfur-oxygen double bond compound are within the scope of this application, the lithium-ion battery has a large number of high-temperature intermittent cycles and a large number of normal-temperature cycles, indicating that the lithium-ion battery has good cycle performance.
[0133] The type and mass percentage of nitrile compounds usually affect the cycle performance of lithium-ion batteries. It can be seen from Examples 1-1, 3-6 to 3-14 that when the type and mass percentage of nitrile compounds are within the scope of this application, the number of high-temperature intermittent cycles of the lithium-ion battery is large, and the number of normal-temperature cycles is large, indicating that the lithium-ion battery has good cycle performance.
[0134] The type and mass percentage of the compound of formula (I) usually affect the cycle performance of the lithium ion battery. It can be seen from Examples 1-1, 3-15 to 3-19 that when the type and mass percentage of the compound of formula (I) are within the scope of this application, the high-temperature intermittent cycle number of the lithium ion battery is large, and the normal temperature cycle number is large, indicating that the lithium ion battery has good cycle performance.
[0135] Different types of electrolytes usually affect the cycle performance of lithium-ion batteries. It can be seen from Examples 4-1 to 4-10 that when the electrolytes combined within the scope of this application are selected, the lithium-ion battery has more high-temperature intermittent cycles and more room-temperature cycles, indicating that the lithium-ion battery has good cycle performance.
[0136] Table 5
[0137]
[0138] The Dv50 of the negative electrode active material usually affects the cycle performance of the lithium-ion battery. It can be seen from Example 1-1, Example 5-1 to Example 5-5, and Example 5-9 to Example 5-10 that when the Dv50 of the negative electrode active material and the surface density of the single-sided negative electrode material layer are within the scope of this application, the lithium-ion battery has a large number of high-temperature intermittent cycles and a large number of normal-temperature cycles, indicating that the lithium-ion battery has good cycle performance.
[0139] The value of N1 / N usually affects the cycle performance of lithium-ion batteries. It can be seen from Examples 1-1, 5-6 to 5-8 that when the value of N1 / N is within the range of this application, the number of high-temperature intermittent cycles of the lithium-ion battery is large, and the number of normal-temperature cycles is large, indicating that the lithium-ion battery has good cycle performance.
[0140] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method or article.
[0141] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0142] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material, and the surface density of the negative electrode material layer on a single surface is D g / 1540.25 mm 2 , 0.100≤D≤0.180; The electrolyte includes fluoroethylene carbonate, and the mass percentage of the fluoroethylene carbonate is A1%, 4.2≤A1≤14.8 based on the mass of the electrolyte; The secondary battery satisfies: 25≤A1 / D≤100.
2. The secondary battery according to claim 1, wherein The electrolyte also includes ethylene carbonate, propylene carbonate and propyl propionate. Based on the mass of the electrolyte, the sum of the mass percentages of ethylene carbonate and propylene carbonate is S1%, the mass percentage of propyl propionate is S2%, 7≤S1≤12, 30≤S2≤70.
3. The secondary battery according to claim 2, wherein: Based on the mass of the electrolyte, the mass percentage M1 of the ethylene carbonate is 2% to 9.5%, and the mass percentage M2 of the propylene carbonate is 2% to 9.5%.
4. The secondary battery according to claim 2, wherein 200≤S2 / D≤650.
5. The secondary battery according to claim 1, wherein The electrolyte further includes a sulfur-oxygen double bond compound, wherein the sulfur-oxygen double bond compound includes at least one of 1,3-propane sultone, vinyl sulfate, propylene sultone, 3-fluoro-1,3-propane sultone, 1,2-propane sultone, 1,4-butane sultone, 1,2-butane sultone, 1,3-butane sultone, 2,4-butane sultone or 1,3-pentane sultone; Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is S3%, 0.01≤S3≤4.9, preferably, 3≤S3≤4.
6.
6. The secondary battery according to claim 1, wherein The electrolyte further includes a nitrile compound, the nitrile compound including at least one of malononitrile, succinonitrile, glutaronitrile, adiponitrile, heptane dinitrile, suberonitrile, 3,3'-oxydipropionitrile, hexane-2-enedinitrile, trans-butylenedinitrile, 2-pentene dinitrile, methylglutaronitrile, 4-cyanopeptane dinitrile, (Z)-but-2-enedinitrile, 2,2,3,3-tetrafluorosuccinonitrile, ethylene glycol bis(propionitrile) ether, 1,3,6-hexanetrinitrile, 1,3,5-pentanetricarbonitrile, 4-(2-cyanoethyl)heptane dinitrile or 1,2,3-tris(2-cyanoethoxy)propane; Based on the mass of the electrolyte, the mass percentage of the nitrile compound is S4%, 2.6≤S4≤8.
2.
7. The secondary battery according to any one of claims 1 to 6, wherein The secondary battery satisfies at least one of the following: (1)4.2≤A1≤8.5; (2) 26.7 ≤ A1 / D ≤ 66.7; (3)32≤S2≤59。 8. The secondary battery according to any one of claims 1 to 6, wherein The secondary battery satisfies at least one of the following: (1)8.5≤A1≤13.5; (2) 55.6 ≤ A1 / D ≤ 76.9; (3)238≤S2 / D≤580.
9. The secondary battery according to any one of claims 1 to 6, wherein The electrolyte satisfies at least one of the following: (1) The electrolyte comprises adiponitrile and ethylene glycol bis(propionitrile) ether; (2) The electrolyte comprises ethylene carbonate, propylene carbonate and succinonitrile; (3) The electrolyte comprises vinyl sulfate and adiponitrile; (4) The electrolyte includes ethylene carbonate, propylene carbonate and 1,3,6-hexanetrinitrile.
10. The secondary battery according to claim 1, wherein The electrolyte also includes a compound of formula (I): wherein X is selected from CR6 or N; R1, R2 and R3 are each independently selected from a hydrogen atom, a halogen, a C2-C5 carbonyl group, a C1-C5 aldehyde group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, a C2-C5 alkynyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heterocycloalkyl group which is unsubstituted or substituted by Ra, a C3-C5 N-heteroaryl group; R4, R5 and R6 are each independently selected from a hydrogen atom, a C1-C5 alkylthio group, a C2-C5 thioether, a C3-C5 N-heterocycloalkyl group, a C3-C5 N-heteroaryl group, a C1-C5 alkyl group which is unsubstituted or substituted by Ra, a C2-C5 alkenyl group which is unsubstituted or substituted by Ra, and a C2-C5 alkynyl group which is unsubstituted or substituted by Ra; The substituents Ra of each group are independently selected from halogen, C1-C5 aldehyde group, C2-C5 carbonyl group, C2-C5 ester group, sulfonic acid group, amino group, C2-C5 amide group or cyano group; Based on the total mass of the electrolyte, the mass percentage of the compound of formula (I) is S5%, 0.01≤S5≤5.
11. The secondary battery according to claim 10, wherein The compound of formula (I) is selected from at least one of the following compounds:
12. The secondary battery according to claim 1, wherein The negative electrode material layer includes a negative electrode active material, and the Dv50 of the negative electrode active material is D1 μm, 5≤D1≤25, preferably, 8≤D1≤15.
13. The secondary battery according to claim 12, wherein: 0.8≤D×D1≤3.4, preferably, 1≤D×D1≤3.
14. The secondary battery according to claim 1, wherein The negative electrode material layer includes negative electrode active material, the number of particles of the negative electrode active material having a sphericity less than or equal to 0.6 and a particle size less than or equal to 10 μm is N1, the total number of particles of the negative electrode active material is N, and N1 / N×100%≤3%. 15 . An electronic device comprising the secondary battery according to claim 1 .